Penilaian Guru Terhadap Pembelajaran Bahasa Arab di MDTA Al-Jihad - Asmar Sholeh; Dwi Haryati; Cahaya Indra; Heppy Ariani Harahap; Ardila Salisa Adristi; Sri Rahmawati; Dea Azka Nadhira Pohan; Sapri Sapri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research explores the evaluation of Arabic language learning by teachers at MDTA Al-Jihad. The study focuses on the teaching methods, challenges faced by the teacher, strategies for motivating students, and initiatives for enhancing students' engagement beyond the classroom. The research was conducted through observations and interviews with Arabic language teacher Najwa Amelia, a 22-year-old graduate in Communication and Islamic Broadcasting from UIN Sumatera Utara.